2017
DOI: 10.1002/eat.22666
|View full text |Cite
|
Sign up to set email alerts
|

Classification of childhood onset eating disorders: A latent class analysis

Abstract: This study tested the hypothesis that latent class analysis (LCA) would successfully classify eating disorder (ED) symptoms in children into categories that mapped onto DSM-5 diagnoses and that these categories would be consistent across countries. Childhood onset ED cases were ascertained through prospective active surveillance by the Australian Paediatric Surveillance Unit, the Canadian Paediatric Surveillance Program, and the British Paediatric Surveillance Unit for 36, 24, and 14 months, respectively. Pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…From the studies that report illness duration at baseline a pattern emerges, although not altogether consistent. The finding that ARFID patients have ususally been ill for a longer time at presentation is supported by several studies (Fisher et al, ; Pinhas et al, ); however, the opposite tendency (Nakai et al, ) or no differences have also been found (Nicely et al, ; Strandjord et al, ) (Table ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…From the studies that report illness duration at baseline a pattern emerges, although not altogether consistent. The finding that ARFID patients have ususally been ill for a longer time at presentation is supported by several studies (Fisher et al, ; Pinhas et al, ); however, the opposite tendency (Nakai et al, ) or no differences have also been found (Nicely et al, ; Strandjord et al, ) (Table ).…”
Section: Resultsmentioning
confidence: 77%
“…The literature review identified only one study utilizing a latent class analysis approach in differentiating between clinical entities (Pinhas et al, ), lending support to a differentiation between ARFID and AN in pediatrics patients. The studies on ARFID and AN epidemiology summarized above also support the distinction between these two diagnostic entities, although they do not apply a latent class analysis approach.…”
Section: Resultsmentioning
confidence: 99%
“…9 A recent latent class analysis of three pediatric surveillance studies (in which pediatricians and child psychiatrists were asked to report on any children < 12 years with a newly diagnosed restrictive type eating disorder) performed across Canada, the United Kingdom, and Australia suggested that one of two identified clusters representing between 25–34% of children with incident restrictive type eating disorders mapped onto symptoms consistent with ARFID. 10 These studies suggest that despite variation in estimates, ARFID is commonly seen in clinical settings and might be common among children in the general population. Further studies are needed to investigate the epidemiology of ARFID in children, adults, and the elderly.…”
Section: What Is Currently Known?mentioning
confidence: 92%
“…Generally, previous studies have reported that those with ARFID present for treatment at a younger age than those with AN (Bryson, Scipioni, Essayli, Mahoney, & Ornstein, ; Cooney et al, ; Fisher et al, ; Forman et al, ; Nakai, Nin, Noma, Teramukai, & Wonderlich, ; Nicely et al, ; Norris et al, ; Ornstein, Nicely, Lane‐Loney, Masciulli, & Hollenbeak, ) and, in outpatient settings, have a longer duration of illness than patients with AN (Fisher et al, ; Forman et al, ). A recent latent class analysis of children between the ages of 5 and 13 presenting to pediatric clinics or general psychological clinics reported that restrictive eating could be separated into two distinct classes: (1) a class similar to AN characterized by body dissatisfaction, fear of gaining weight, and over exercising; and (2) a class similar to ARFID characterized by somatic concerns and low levels of weight and shape concerns (Pinhas et al, ). Consistent across three samples from English‐speaking countries (United Kingdom, Australia, and Canada), the class similar to ARFID was younger with elevated levels of anxiety and, though not statistically significant, a longer duration of illness (Pinhas et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent latent class analysis of children between the ages of 5 and 13 presenting to pediatric clinics or general psychological clinics reported that restrictive eating could be separated into two distinct classes: (1) a class similar to AN characterized by body dissatisfaction, fear of gaining weight, and over exercising; and (2) a class similar to ARFID characterized by somatic concerns and low levels of weight and shape concerns (Pinhas et al, ). Consistent across three samples from English‐speaking countries (United Kingdom, Australia, and Canada), the class similar to ARFID was younger with elevated levels of anxiety and, though not statistically significant, a longer duration of illness (Pinhas et al, ). Interestingly, at higher levels of care, child and adolescent patients with ARFID have often shown similar illness duration to patients with AN (Nicely et al, ; Ornstein, Essayli, Nicely, Masciulli, & Lane‐Loney, ; Strandjord, Sieke, Richmond, & Rome, ).…”
Section: Introductionmentioning
confidence: 99%